Metallothionein analysis and cell damage levels on the liver and gill Of Barbonymus gonionotus In Brantas River, Indonesia - Alfiah Hayati; Nita Yuliarini; Agoes Soegianto; Hana Widyana; Inesavira Rindaputri; Nuris Auliya; Putri Ayu Ika (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2017)
This study aimed to analyze the levels of metallothionein and damage to hepatocytes and gills of Barbonymus gonionotus in the Brantas River (upstream and downstream), and the correlation levels of metallothionein in the gills and liver of Barbonymus gonionotus with different sampling time variation (March, June, and September 2016). Fishes were caught using trawl in two stations (Karangkates Reservoir and the Kali Jagir river). Fish gills and livers were taken for histopathological analysis and levels of metallothionein were measured by ELISA method. Gills histopathological analysis showed that the highest damage in Karangkates reservoir dan Kali Jagir river is hyperplasia. Liver histopathological analysis in Karangkates reservoir showed normal hepatocytes meanwhile necrosis is highest damage found in Kali Jagir river. Metallothionein levels of fish in Karangkates reservoir for March, June, and September were 0.18 ng/mL; 0,18 ng/mL; and 0.2 ng/mL (gills fish); 0,18 ng/mL; 0,34 ng/mL; and 0,21 ng/mL (liver fish) respectively. Metallothionein levels of fish in Kali Jagir river for March, June, and September were 0,26 ng/mL; 0,18 ng/mL; and 0,18 ng/mL (gills fish); 0,2 ng/mL; 0,45 ng/mL; 0,19 ng/mL (liver fish) respectively. We conclude that the damage to the gills and liver of Barbonymus gonionotus was mostly found in Kali Jagir River and the highest metallothionein level of Barbonymus gonionotus also presented in Kali Jagir River.